Educação ambiental : uma realidade por meio da aplicação da oficina “Sou Eco 13” como recurso pedagógico no ensino de ciências - Oliveira, Patricia Machado (2015)
This paper presents and applies the workshop "I am'm Eco 13" as a pedagogical tool in teaching science , specifically in Environmental Education , in order to survey the environmental perceptions of students and community representatives , as well as strengthen the feeling of belonging of these participants. A story context was performed , reporting the socioeconomic development process of the city of Nova Guarita - MT , where the activities were performed . We work in partnership with students of the Third Cycle and High School , in the Escola Estadual 13 de Maio, during the school years 2013 and 2014. We used as methodological support the guiding principles of Critique Aaction Rresearch Critique. Data were analyzed qualitatively and collected by open questionnaire , semi-structured interviews and notes taken in class . The questionnaires allowed accomplish an overview of the environmental perceptions of students . With this information debates guided them , and then we developed the workshop , which presented two steps: "Dreams tree" and " Stones in the way ." Finally the students were instructed to interview people in the community , the older preference and that they lived the longest in the city . The workshop proved to be an effective pedagogical feramente tool in EEEA, in that it achieved the expected goals , was an innovative practice , dynamic , dialogic and therefore well accepted by the students.